International Business Negotiations between Finnish and Chinese business people: A Cultural Approach - Vekara, Johanna (My University, 2014)
International companies nowadays have vast operations in China. Furthermore, international business negotiations between Western and Chinese companies have increased rapidly during the past couple of decades. Understanding the Chinese culture thus has become vital to Western negotiators. Finnish corporations also have intensive cooperation with the Chinese corporations, Finnish businesses have subsidiaries in China and future business assets for Finnish companies are in China. Finnish-Chinese business negotiations have not yet been studied, therefore this thesis attempts to fill this research gap. Firstly, cultural comparison of Finnish and Chinese cultures is done through project GLOBE research selected cultural dimensions (performance orientation, future orientation, individualism vs. collectivism, power distance, uncertainty avoidance). Both Finnish and Chinese cultures and business behavior as well as previous negotiation research findings are presented. Secondly, empirical research was conducted through semi-structured qualitative interviews of eight high level Finnish business executives with extensive personal experience negotiating with the Chinese. The interview data was analyzed through content analysis and inductive categorization method, where similar responses of all interviewees were categorized together. According to this study Finnish and Chinese get along well in the international business negotiations. The most important Chinese cultural factors, face (mianzi) and relationships (guanxi), both were discovered to have great impact on Finnish-Chinese business negotiations. Altogether eight factors were found to impact Chinese negotiations: the Chinese government, Chinese politics, Chinese negotiation tactics, face, relationships, language barriers, understanding problems, and individual characteristics of the Chinese people. All these factors a Finnish negotiator has to take into consideration before entering into Chinese negotiations. Furthermore, this study provides practical guidelines for Finnish managers entering into Chinese negotiations and list of qualities a competent Finnish negotiator should have.
Keywords: International business negotiation; Finland; China; culture; cultural differences; intercultural; guanxi; mianzi; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Master's Degree Programme in International Business|